THE EFFECT OF MARKETING CAPABILITIES UPON ACHIEVING MARKETING EXCELLENCE - Ali Abdul Wahid Jassim; Rabie Yassin Saud (Scholar Express Journals, 2022)
This study tries to pinpoint the contribution made by marketing talents to raising markers of marketing excellence. Given how crucial the interaction between these two factors is for production or service companies. Organizations must adopt this concept to be able to achieve marketing excellence. The researcher dealt with the issue of marketing capabilities as an independent variable with its dimensions (price, promotion, distribution, and product). Marketing excellence as a dependent variable, a hypothesis was developed for research that reflects the nature of the correlation and influence between pricing on the one hand and marketing excellence on the other. A number of main hypotheses were tested using the statistical program (SPSS) for the data obtained through the questionnaire form that was distributed to a sample of workers in the soft drinks company in Baghdad. The research reached a set of conclusions, the most important one is that there is a correlation relationship and a moral effect on marketing capabilities and their impact on achieving marketing excellence.
Keywords: marketing; number; correlation; capabilities